Dataset: Deterministic optical polarisation in nitride quantum dots at thermoelectrically cooled temperatures - Wang, T; Puchtler, T; Patra, S; Schulz, S; Taylor, R (University of Oxford, 2017)
These data were created in order to assess the high temperature polarisation properties of a-plane InGaN quantum dots, in micro-photoluminescence experiments and kp band simulations, from 2015 to 2017. OriginPro has been used to analyse the data.